Powerful knowledge and the significance of teaching geography for in-service upper secondary teachers – a case study from Northern Finland. Issue 2 (3rd April 2019) - Virranmäki, Eerika; Valta-Hulkkonen, Kirsi; Rusanen, Jarmo
Abstract: The aim of this research is to ask what kind of geography is taught in Finnish upper secondary schools and whether this knowledge is powerful knowledge. This is achieved by analysing 11 in-service geography teachers' concept maps and in-depth interviews with qualitative data analysis. The results indicate the dominance of three terms: spatiality, phenomena and a holistic approach running through the teachers' conceptions of geographical knowledge, skills and assessment. Geography is described by the teachers as a science which studies extensive spatial phenomena with the help of concepts and a holistic approach and in which values and students' own lived experiences play a major role. We conclude that the in-service Finnish upper secondary teachers' perceptions of geography are a form of powerful knowledge because they: (1) urge students to form new geographical thinking about the world, (2) give possibilities for students to study geographical phenomena and (3) evaluate their own knowledge, (4) encourage students to follow topical debates in different scales, (5) open up the students' world views and (6) support the general objectives of Finnish upper secondary schools by applying four of the six cross-curricular themes to a great extent in teaching geography, particularly sustainable development.